Pembelajaran PPKn melalui Permainan Papan Edukatif: Mengatasi Tantangan Perbedaan Gaya Belajar Siswa dan Meningkatkan Pemahaman Pancasila - Alisya Roisatul Ummah; Fathurrohman (Tumoutou Social Science Journal, 2026)
Pancasila and Civic Education (PPKn) learning in elementary schools plays an important role in shaping students' character and understanding of Pancasila values. However, the implementation of learning often faces challenges due to differences in students' learning styles, resulting in some students being less actively involved and their learning outcomes not being optimal. This study aims to examine the effectiveness of using educational board games as an alternative learning medium that can be adapted to various student learning styles and improve understanding of Pancasila values. The method used in this study is a literature review, examining various articles, journals, and previous research results that discuss the implementation of educational games in the context of PPKn learning and character education. The results of the study show that educational board games can create an interactive, collaborative, and contextual learning atmosphere, thereby stimulating visual, auditory, and kinesthetic learning styles in a balanced manner. In addition, this medium is considered effective in helping students understand moral concepts and Pancasila values through meaningful play experiences. The conclusion of this study is that civic education learning through educational board games has the potential to be a strategic innovation in overcoming differences in student learning styles while improving the understanding and application of Pancasila values in elementary schools.